2013
DOI: 10.1038/srep03022
|View full text |Cite
|
Sign up to set email alerts
|

Sirt6 regulates postnatal growth plate differentiation and proliferation via Ihh signaling

Abstract: Sirtuin 6 (Sirt6) is a mammalian homologue of NAD 1 -dependent histone deacetylase Sir2. Although Sirt62/2 mice exhibit growth retardation, the role of Sirt6 in cartilage metabolism is unclear. The aim of this study was to investigate the Sirt6 signaling pathway in cartilage metabolism. Immunohistological evaluation of the tibial growth plate in Sirt62/2 mice exhibited impaired proliferation and differentiation of chondrocytes, reduced expression of Indian hedgehog (Ihh), and a senescent phenotype. When Sirt6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…On the contrary, activating transcription factor 4 (ATF4) can activate the transcription of Ihh by binding to its promoter ). Sirtuin 6 may regulate Ihh expression by increasing the affinity of ATF4 for the Ihh promoter (Piao et al 2013).…”
Section: Ihh Signalingmentioning
confidence: 99%
“…On the contrary, activating transcription factor 4 (ATF4) can activate the transcription of Ihh by binding to its promoter ). Sirtuin 6 may regulate Ihh expression by increasing the affinity of ATF4 for the Ihh promoter (Piao et al 2013).…”
Section: Ihh Signalingmentioning
confidence: 99%
“…Thus, in SIRT6 null mice, the heights of each of the different zones of the GP and of the primary spongiosa are reduced. Studies by Piao et al [170] pointed to the role of Ihh activation in SIRT6 action on cell proliferation. SIRT6 binds to the Ihh promoter in primary chondrocytes, and Ihh is a downstream target of SIRT6 in chondrogenesis.…”
Section: Local Molecular Mechanisms In Malnutrition and Cu Growthmentioning
confidence: 99%
“…Because recent reports have suggested that SIRT6 regulates Hh signaling [5], and because DHA can also modulate Hh signaling [28], we examined the potential involvement of Hh signaling in SIRT6-mediated apoptosis induced by DHA. Firstly, to confirm that DHA modulates Hh signaling in NSCLC cells, the mRNA and protein expression levels of Hh signaling molecules were assessed by reverse transcription-PCR (RT-PCR) and western blot analysis.…”
Section: Dha-induced Sirt6 Activation Is Associated With Downregulatimentioning
confidence: 99%
“…SIRT6 is localized in the nucleus [1] and has two types of enzymatic activities: mono-adenosine diphosphate ribosyltransferase [3] and deacetylase [4] activities, both of which are dependent on nicotinamide adenine dinucleotide [5]. SIRT6 regulates various cellular processes, including telomere maintenance, repair of damaged DNA, aging, immunity, and glucose homeostasis, and is important in cancer [3,[6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation